(untitled) (e-Journal of Linguistics, 2019)
The palm-leaf manuscript of Cilinaya is one of the manuscripts which is still implemented in the life of the Sasak ethnic people. The writer conveyed massages to the readers using different figurative expressions, one of which is metaphor. This current study is a product- oriented translation study in which the qualitative descriptive approach was applied. The palm- leaf manuscript of Cilinaya was used as the data source. Based on the result of analysis and discussion, it can be concluded that several metaphorical expressions are used to praise a beautiful girl that everybody is proud of. Those metaphorical expressions are Duh mas mirah kembang mete, Duh mas mirah serining kasur, Duh mas mirah buaq bulu, Neneq bini, Dun den dare masku, Dendare, dende, Duh mas mirah dende ayu. In the Sasak language, a metaphor will have different function and meaning if the morpheme „be‟ is inserted in the expression „lauh daye’ to form „belauk bedaye‟.